Molly's story eaudiobook A dog's purpose novel. - Cameron, W. Bruce (Tantor Media, 2017)
Meet Molly—a very special dog with a very important purpose. This is an irresistible book for young listeners adapted from A Dog's Journey , the sequel to the bestselling A Dog's Purpose (now a major motion picture). Molly knows that her purpose is to take care of her girl, C.J., but it won't be easy. Neglected by her mother, Gloria, who won't allow her to have a dog, C.J. is going through some tough times. Molly's job is to stay hidden in C.J.'s room, cuddle up to her at night, and protect her from bad people. And no matter what Gloria does to separate them, nothing will keep Molly away from the girl that she loves.